Determinants of hypofibrinolysis in patients with digestive tract cancer - Gronostaj, Katarzyna; Richter, Piotr; Nowak, Wojciech; Undas, Anetta (Gastroenterology Review/Przegląd Gastroenterologiczny, 2016)
Introduction : Recently, we demonstrated that digestive tract cancer (DTC) is associated with reduced fibrin clot permeability and impaired fibrinolysis. Aim : We investigated determinants of fibrinolysis in DTC patients. Material and methods: In 44 consecutive patients with DTC and 47 controls matched for age, sex, and cardiovascular risk, we evaluated fibrinolysis proteins, platelet activation markers, thrombin formation, together with plasma clot lysis time assays in the absence (CLT) and presence of carboxypeptidase potato inhibitor (CLT CPI) that blocks thrombin activatable fibrinolysis inhibitor (TAFI). Results : In the DTC group CLT (by 22.3%) and CLT CPI (by 27.4%) were longer compared with controls. The DTC patients had higher plasma fibrinolysis inhibitors, plasminogen activator inhibitor 1 (PAI-1) (by 18.2%), TAFI activity (by 17.3%), and antigen (by 11.2%). The patients had markedly increased platelet markers – soluble CD40 ligand (by 338%) and P-selectin (by 97%), together with von Willebrand factor (vWF) antigen (by 61%). Thrombin-antithrombin complexes (TAT) (by 48.7%) and soluble thrombomodulin (sTM) (by 17.2%) were also increased in the DTC group (all p < 0.05). Patients with high-grade tumours (n = 26) compared with remainders (n = 18) had longer CLT, higher tissue-type plasminogen activator antigen, both TAFI antigen and activity levels, vWF, and sTM. Multiple regression analysis after adjustment for potential confounders showed that independent predictors of CLT in DTC patients were TAT, TAFI activity, and vWF. The only independent predictor of CLT CPI was TAT. Conclusions : Hypofibrinolysis in DTC patients is largely driven by enhanced thrombin generation, TAFI, and endothelial injury.